DETERMINASI TINGKAT PENGUNGKAPAN WAJIB LAPORAN KEUANGAN PEMERINTAH DAERAH PROVINSI PULAU SUMATERA - Aliyah, Ade Zahrah; Zulkifli, Zulkifli; Oktarida, Anggeraini (Universitas Muhammadiyah Tangerang, 2024)
This research aims to analyze the level of dependency, financial independence ratio, number of OPDs, and audit findings in relation to the mandatory disclosure level of Local Government Financial Statements (LKPD) on Sumatera Island from 2018 to 2022. The study population includes all provinces on Sumatera Island, with sample data collected using a saturation technique, resulting in a sample size of 50 LKPD from the 2018-2022 BPK-RI Audit Results Report. The independent variables investigated are the degree of dependency, financial independence ratio, number of OPDs, and audit findings, While the mandated disclosure level of LKPD is the dependent variable. Multiple linear regression analysis and secondary data are used in the present research, which is processed using SPSS version 25. The findings reveal that the level of dependency, financial independence ratio, number of OPDs, and audit findings partially significantly influence the mandatory LKPD disclosure level. The search results show that the level of dependency, financial independence ratio, number of OPDs, and audit findings simultaneously significantly influence the mandatory LKPD disclosure level